ANALISIS PENGARUH KECUKUPAN MODAL (CAR), LIKUIDITAS (FDR) TERHADAP PROFITABILITAS PADA BANK MUAMALAT (Periode 2016-2020) - Ajeng Febri Setyarini; Muhammad Iqbal Fasa; Suharto Suharto (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
Banking institutions are one of the activator of a country's economy, namely business entities that collect funds from the public in the form of deposits and channel them back to the public in the form of credit. Efficient and optimal fund collection and distribution conducted by banks will be in line with the main objective of banking, namely achieving a level of profitability. Therefore, banks need to maintain profitability in order to remain stable or even increase. Return on Asset (ROA) is used as a proxy in measuring the profitability of a bank. A fairly complex problem in bank operational activities is liquidity management, due to the existence of funds managed by banks, most of which are short-term funds obtained from the public and can be withdrawn at any time. The purpose of this study is to obtain findings regarding the effect of capital adequacy ratio (CAR) and liquidity on profitability . The research method is to use quantitative research with secondary data, namely where the data that has been published with data collection using documentation techniques and analysis techniques using explanatory research methods. The results showed that capital adequacy ratio (CAR) and liquidity partially had a positive and insignificant effect on profitability while simultaneously had a significant effect on profitability.